A double seismic zone in the subducting Juan Fernandez Ridge of the Nazca Plate (32°S), central Chile. Issue 7 (8th July 2013) - Marot, M.; Monfret, T.; Pardo, M.; Ranalli, G.; Nolet, G.
Abstract [1] The region of central Chile offers a unique opportunity to study the links between the subducting Juan Fernandez Ridge, the flat slab, the double seismic zone (DSZ), and the absence of modern volcanism. Here we report the presence and characteristics of the first observed DSZ within the intermediate‐depth Nazca slab using two temporary seismic catalogs (Ovalle 1999 and Chile Argentina Seismological Measurement Experiment). The lower plane of seismicity (LP) is located 20–25 km below the upper plane, begins at 50 km depth, and merges with the lower plane at 120 km depth, where the slab becomes horizontal. Focal mechanism analysis and stress tensor calculations indicate that the slab's state of stress is dominantly controlled by plate convergence and overriding crust thickness: Above 60–70 km depth, the slab is in horizontal compression, and below, it is in horizontal extension, parallel to plate convergence, which can be accounted for by vertical loading of the overriding lithosphere. Focal mechanisms below 60–70 km depth are strongly correlated with offshore outer rise bend faults, suggesting the reactivation of preexisting faults below this depth. The large interplane distances for all Nazca DSZs can be related to the slab's unusually cold thermal structure with respect to its age. Since LPs globally seem to mimic mantle mineral dehydration paths, we suggest that fluid migration and dehydration embrittlement provide the mechanism necessary to weaken the rock and that the stress field determines the direction of rupture.